KEPUASAN KERJA DAN KINERJA PEGAWAI TERHADAP KEPUASAN PASIEN: KUALITAS LAYANAN SEBAGAI VARIABEL MEDIASI - Maujud S Maya; Aldina Shiratina; Abdullah W Jabid (Jurnal Manajemen Sinergi, 2021)
ABSTRACTObjective: The purpose of this study is to find out and analyze: (1) the effect of Job Satisfaction affects the quality of service; (2) the effect of Job Satisfaction affects patient satisfaction; (3) the effect of employee performance affects the quality of service; (4) the effect of Service Quality influences patient satisfaction; (5) Service Quality mediates the effect between Job Satisfaction and Patient Satisfaction; and (6) the influence of Service Quality mediates the effect between employee performance and patient satisfaction. The number of research samples are 90 employees. Methodology: The test instrument used was a structural equation model (SEM) using Partial Least Square (PLS) as a statistical test tool. Finding: H1, H2, no accepted, while H3, and H4 are accepted at the 5% confidence level. Hypothesis 5 no mediates, but H6 fully mediated the effect between nurse performance.Conclusion: The results showed that: (1) Job satisfaction did not have a positive and significant effect on service quality; (2) Job satisfaction does not have a positive and significant effect on patient satisfaction; (3) Employee / Nurse Performance has positive and significant effect on the quality of services; (4) Service Quality has positive and significant effect on patient satisfaction; (5) Service quality does not mediate the effect between job satisfaction and patient satisfaction; and (6) Quality of service mediates the effect between employee / nurse performance and patient satisfaction at the Inpatient Health Center in Ternate City.Â